A Study about Major Industrial Regions of India: Exploring the Factors and Impacts of Industrial Clustering in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Industrial regions emerge when a number of industries locate close to each other and share the benefits of their closeness. They tend to concentrate on certain locations because of the favorable local factors. Several indices are used to identify the clustering of industries, important among them are•The number of industrial units•Number of industrial workers.•Quantum of power used for industrial purposes.•Total industrial output.•Value added by manufacturing, etc.